Propuesta de un plan de mejoramiento basado en indicadores para el proceso logístico de una empresa de distribución de alimentos (2020)
Logistics indicators are of vital importance to organizations because they facilitate the measurement, monitoring, and analysis of each of the company's processes; in addition, they serve as a basis for the construction of strategies that lead to the achievement of corporate objectives. Food Distributor is a company dedicated to the marketing of food for human consumption throughout the Colombian territory; due to the nature of its activities, the need to develop and implement a proposal for improvement in the logistics process was identified, which improves performance in terms of cost, time and optimization of physical, economic and human resources.